2016
DOI: 10.1016/j.fuel.2016.04.102
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical water gasification of RDF and its components over RuO2/γ-Al2O3 catalyst: New insights into RuO2 catalytic reaction mechanisms

Abstract: Five samples, including a composite refuse derived fuel (RDF) and four combustible components of municipal solid wastes (MSW) have been reacted under supercritical water conditions in a batch reactor. The reactions have been carried out at 450 °C for 60 min reaction time, with or without 20 wt% RuO2/gamma-alumina catalyst. The reactivities of the samples depended on their compositions; with the plastic-rich samples, RDF and mixed waste plastics (MWP), giving similar product yields and compositions, while the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The high conversion of eucalyptus wood chips at 450 and 500 • C indicates that efficient interactions occurred between the NiFe 2 O 4 catalytic surface and reactant the molecules at these temperatures. According to Azadi et al [42] the use of smaller catalyst particles, as in the present work (18 nm), can reduce the diffusion path and consequently enhance the catalyst performance, as previously reported by other researchers [43][44][45]. Our results confirmed that the NiFe 2 O 4 powder prepared by the combustion reaction was active as a catalyst for SCWG and may be useful for moderate temperature processes.…”
Section: Catalytic Testing Of Nife 2 O 4 For Scwg Of Eucalyptus Chipssupporting
confidence: 89%
See 3 more Smart Citations
“…The high conversion of eucalyptus wood chips at 450 and 500 • C indicates that efficient interactions occurred between the NiFe 2 O 4 catalytic surface and reactant the molecules at these temperatures. According to Azadi et al [42] the use of smaller catalyst particles, as in the present work (18 nm), can reduce the diffusion path and consequently enhance the catalyst performance, as previously reported by other researchers [43][44][45]. Our results confirmed that the NiFe 2 O 4 powder prepared by the combustion reaction was active as a catalyst for SCWG and may be useful for moderate temperature processes.…”
Section: Catalytic Testing Of Nife 2 O 4 For Scwg Of Eucalyptus Chipssupporting
confidence: 89%
“…The increase in methane concentration could be due to both methanation (exothermic) of carbon oxides (CO x ) and demethylation (endothermic) of larger molecules in the liquid products. The latter is supported by the overall increase in the biomass gasification at the higher temperature, 500 • C. In the presence of the catalyst, the increase in the overall biomass gasification also showed the influence of the catalyst in converting the liquid and solid products to gases [4,32,[43][44][45]. Table 2 provides good evidence that both the water-gas shift reaction and methane reforming occurred, forming increased concentrations of CO 2 and H 2 .…”
Section: Catalytic Testing Of Nife 2 O 4 For Scwg Of Eucalyptus Chipsmentioning
confidence: 77%
See 2 more Smart Citations
“…During the reaction, heavy oil generally begins to decompose at around 370 °C, and the condensation reaction accelerates as increase of pyrolysis temperature. [33] The pyrolysis of alkanes in petroleum sludge mainly includes the formation of small molecular alkenes and secondary alkanes after the C-C bond is broken and the formation of alkenes with a constant carbon number after the C-H bond is broken. The general formula can be expressed as: [34] R-CH2CH2-R' → R-CH=CH2 + R'H…”
Section: The Main Compositions and Pyrolysis Of Petroleum Sludgementioning
confidence: 99%